Regional Geopolitical Trends and the Dismemberment of Pakistan: Assessment of Relevant Events during 1965-72: Geopolitical Trends and the Dismemberment of Pakistan - Khurshaid (The Journal of Humanities & Social Sciences, 2021)
Pakistan was dismembered in 1971 after a civil war in its eastern wing, followed by Indian intervention. The regional and global geopolitics of the time played a vital role in the division of the country into two parts. Geopolitical complexities and the corresponding priorities of the stakeholders got involved into the separation of East Pakistan- now called Bangladesh. The process of the dismemberment precipitated after Indo-Pak war of 1965 which had caused fears of insecurity amongst the people of Bengal. The fears were exploited by the geopolitical forces that finally caused the fall of Dhaka. The story of the fall of Dhaka was accomplished when India and Pakistan signed Simla Agreement in 1972. This paper focuses on the geopolitical dimension of the turmoil period and its endpoint till the creation of Bangladesh. The study is conducted through qualitative methods of secondary data analysis. The secondary data is analyzed under the standards of the thematic approach. A theoretical model of geographical determinism is applied to understand how geopolitics contributed in the dismemberment of Pakistan. Saul B. Cohen’s model of Shatter belts is helpful in this regard. Shatter belts are the volatile geographical areas that are polarized in ways that determine the politics of the surrounding region/s. In a nutshell, the study combines history with the political expression of geography to know geopolitics as one of the causes responsible for the dismemberment of Pakistan. The study applies secondary data analysis as it is constrained by access to primary data, found in the official files of the stakeholder countries. Still, it is an attempt to understand the dismemberment phenomenon through the involved geopolitical lenses.